UJI DAYA HAMBAT EKSTRAK DAUN SEMBUKAN (Paederia foetida) TERHADAP Vibrio cholerae - Fer Hidayat, Adelya; Selamet Duniaji, Agus; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i04.p04, 2020)
Sembukan leaf (Paederia foetida) is one of a tropical Asian plant that contains bioactive compounds and often used as functional foods. The aim of this research was to determine the concentration of flavonoid compounds sembukan leaf (Paederia foetida) as well as the concentration of inhibitory against the growth of Vibrio cholerae. This study uses an experimental design with 5 kinds concentrations : 20%, 40%, 60%, 80%, and 100%, with three replications. The analysis were repeated 3 times resulting in 15 experimental units. The data were presented in descriptive statistic in the form of tables and figures. The results showed that the sembukan leaf extract contained flavonoid compounds of 1.18%. The extract concentration of 80% exerted the highest inhibitory activity against V. cholerae classified as strong with a diameter zone inhibition of 19.60 mm. The sembukan leaf has percentage inhibition in the range of 15.36% - 64.86% with bacteriostatic category.